An Exploratory Study of Clinical Efficacy of “Shwasahar Dashemani” in Shwas Roga - Kumar, Savan; Dipti (International Research Journal of Ayurveda & Yoga, 2022)
Shwasa is considered as the most serious disease in Ayurveda and stated that none other disease kills as instantaneously as Shwasa. A high prevalence of respiratory disorders was observed in Delhi, 30.5 % people are affected the respiratory ailments. Shwasahar Mahakasaya is one of the significant Ayurveda group of medicine which helps in improving Respiratory diseases. Study is to drill down the possible effect of Shwasahar Mahakasaya based on distribution of active principles explained in Ayurveda classical text. Percentage criteria is being analysed to get the clarity about the reason behind desired output. Rasa, Guna, Virya and Vipaka these attributes are analyzed based on their component distribution. Distribution of dominating attributes among 10 Plants indicated in Shwashhar Mahakasaya are Katu Tikta Rasa, Laghu Guna, Ushna Virya and Katu Vipaka. Results found out of the study is 31.82 % Katu Rasa, 36.36 Tikta Rasa, 43.48% Laghu Guna, 60.00% Ushna Virya and 60.00% Katu Vipaka. Ushna Virya of the drugs is responsible to alleviate Vata and the remaining other factors Laghu Guna, Katu Tikta Rasa and Katu Vipaka along with Ushna Virya is responsible to alleviate Kapha. Equal potency in Rasapanchaka will produce final result in sequential manner where each aspect lined up with basic effects of Rasa. That is the best possible reason to get the great outcome through Shwashar dashemani.